Early Mortality of Prostatectomy vs. Radiotherapy as a Primary Treatment for Prostate Cancer: A Population-Based Study From the United States and East Germany - Medenwald, Daniel; Vordermark, Dirk; Dietzel, Christian T. (Frontiers in Oncology, 2020)
Objective: To assess the extent of early mortality and its temporal course after prostatectomy and radiotherapy in the general population. Methods: Data from SEER-database and East German epidemiologic cancer registries were used for the years 2005-2013. Metastasized cases were excluded. Analysing overall mortality, year-specific Cox regression models were used after adjusting for age (including age squared), risk stage and grading. To estimate temporal hazards we computed year-specific conditional hazards for surgery and radiotherapy after propensity-score matching and applied piecewise proportional hazard models. Results: In German and US-American populations we observed higher initial three-month mortality odds for prostatectomy (USA: 9.4, 95% CI: 7.8–11.2; Germany: 9.1, 95% CI: 5.1-16.2) approaching the null effect value not before 24 months (estimated annual mean 36 months in US data) after diagnosis. During the observational period we observed a constant hazard ratio for the 24-month mortality in the US-population (2005: 1.7, 95% CI: 1.5–1.9; 2013: 1.9, 95% CI: 1.6–2.2) comparing surgery and radiotherapy. The same was true in the German cohort (2005: 1.4, 95% CI: 0.9–2.1; 2013: 3.3, 95% CI: 2.2–5.1). Considering low-risk cases, the adverse surgery effect appeared stronger. Conclusion: There is strong evidence from two independent populations of a considerably higher early to midterm mortality after prostatectomy compared to radiotherapy extending the time of early mortality considered by previous studies up to 36 months